Sustainable farmers, deficient State? Self-reported agricultural sustainability in the Argentine Chaco region - Lucas Seghezzo; Laura Liliana Huaranca; Mónica Liliana Vega; Gabriela Virginia Jeckeln; Marcela Andrea Avalos; Martín Alejandro Iribarnegaray; José Norberto Volante; Federico Hernán Mónico Serrano; Matías Mastrangelo; Zhanli Sun; Daniel Müller (International Journal of Agricultural Sustainability, 2020)
Unsustainable production systems can exacerbate the negative consequences of deforestation and land use change, increasing the vulnerability of local populations to environmental or economic crises. We developed and applied a participatory method to assess the sustainability of agricultural production systems in the Chaco region of Northern Argentina. We used a combination of theoretical, methodological, and analytical approaches. The theoretical foundation of our study was Elinor Ostrom's general framework for analyzing the sustainability of social-ecological systems (SESs). Our main methodological tool was a participatory, empirical, semi-quantitative multi-criteria decision making methodology based on expert meetings, field trips, and semi-structured interviews. We also made use of a political ecology approach to situate our case study and put our empirical results in perspective by relating them to issues of power and environmental justice. Our findings suggest that local farmers perceive their production systems as barely sustainable, with variables such as type of activity and farm size, among others, clearly influencing their sustainability estimations. Sustainability seems dependent on the skills and organization abilities of local farmers, with the State failing to provide sufficient basic infrastructure and enabling services. Our method could inform policy making aimed at improving the sustainability of agricultural practices in the region.